Outdoor and accelerated weathering of acrylonitrile-butadiene-styrene : a correlation study - Santos, R. M. (2013)
The influence of outdoor and accelerated weathering conditions on the photo-oxidative degradation of stabilized acrylonitrile-butadiene-styrene (ABS) was investigated, aiming to establish a correlation between both weathering types. ABS samples containing combinations of light stabilizers (ultraviolet absorbers e UVA and hindered amine light stabilizers e HALS) and antioxidants were prepared by melt compounding, exposed to different weathering conditions and characterized by infrared spectroscopy and quasi-static measure ments. The results obtained by infrared spectroscopy and quasi-static measurements are in good agreement, showing that the Q-Sun Xe-3-Hs resembles the outdoor weathering phenomena. Applying a shift factor of 0.85 MJ m 2 to the abscissa axis, it was found that the exposure of stabilized ABS samples to ca. 1260 h in Q-Sun Xe-3-Hs induces changes in its mechanical performance, which corresponds to one year of outdoor exposure at Lisbon